2016
DOI: 10.1177/1359105315596371
|View full text |Cite
|
Sign up to set email alerts
|

The pain of being misunderstood: Invalidation of pain complaints in chronic low back pain patients

Abstract: A particular form of social pain is invalidation. Therefore, this study (a) investigates whether patients with chronic low back pain experience invalidation, (b) if it has an influence on their pain, and (c) explores whether various social sources (e.g. partner and work) influence physical pain differentially. A total of 92 patients completed questionnaires, and for analysis, Pearson's correlation coefficients and hierarchical linear regression analyses were conducted. They indicated a significant association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…In line with the model, validation training was in a recent study found to increase the frequency of validating responses while decreasing invalidating responses, and this had a positive effect on emotions in the person with pain [2]. Further, a significant association was in another study found between invalidation from the partner and pain disability [37]. A possible consequence of a pattern of invalidating responses is marital conflict.…”
Section: Research Findings the Significance Of Affective Interactionmentioning
confidence: 71%
See 1 more Smart Citation
“…In line with the model, validation training was in a recent study found to increase the frequency of validating responses while decreasing invalidating responses, and this had a positive effect on emotions in the person with pain [2]. Further, a significant association was in another study found between invalidation from the partner and pain disability [37]. A possible consequence of a pattern of invalidating responses is marital conflict.…”
Section: Research Findings the Significance Of Affective Interactionmentioning
confidence: 71%
“…A few studies on validating and invalidating partner responses have recently been presented. Findings indicate that validation is associated with decreases in negative affect [2] and that invalidation is associated with higher pain disability [37]. As it leads to opposite predictions from those of the operant model when it comes to the effect of negative/invalidating partner responses, the model might explain some of the mixed results observed within the operant framework.…”
Section: Discussionmentioning
confidence: 93%
“…This was reported with both high (macro) and microdoses. Effect duration varied and ranged from no relief beyond the acute experience to over a year-most contributors (8), regardless of dose taken, reported feeling reductions in pain for at least 3-5 days following their experience, with pain levels gradually increasing over time. Other changes were longer lasting though; most contributors (9) reported enduring increases in positive embodiment and interoception, which inspired a desire to treat the body better in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the current findings highlight a number of key issues in the parental injustice experience that are not captured in the adult, intrapersonal framework as proposed by Sullivan and colleagues (Sullivan et al., 2008). Specifically, no explicit reference is made to interpersonal injustice, even though its importance for patients’ well‐being has been documented in previous work (Walker & Pettigrew, 1984; Jordan et al., 2007; Jordan et al, 2011; McParland et al., 2011; Ferris et al., 2012; Karos, 2017; Wernicke, de Witt Huberts, & Wippert, 2017; Karos et al., 2018). Given this interpersonal dimension and the fact that maternal accounts described frequent negative interactions with health care providers, research may also benefit from studies focusing on other perspectives than that of the parent (e.g.…”
Section: Discussionmentioning
confidence: 99%